Large-scale genomic deletion in spl39 activates immune responses and confers resistance to rice bacterial blight - Fang, Cheng; Ma, Wei; Zhu, Xiaotong; Peng, Lingling; Tao, Liangzhi; Zhao, Zhiqiang; Wang, Fengbin; Ye, Yafeng; Ma, Bojun; Wu, Yuejin; Yuan, Jie; Liu, Binmei; et al. (Frontiers in Plant Science, 2025)
Lesion mimic mutants (LMMs) are invaluable for uncovering the molecular mechanisms of programmed cell death (PCD) and plant immunity and identifying more LMMs expands our understanding of these complex processes. In this study, we characterized a novel rice LMM, spl39, identified through heavy-ion beam irradiation. The spl39 mutant exhibits reddish-brown lesions from the tillering stage, reduced plant height, grain size, and fertility. Chloroplast ultrastructure analysis revealed thylakoid disruption and membrane damage, contributing to reduced photosynthetic capacity. Excessive ROS accumulation and reduced antioxidative enzyme activities triggered PCD. Genetic mapping identified a 306-kb deletion in spl39, encompassing 33 genes, including 12 from the diterpenoid biosynthesis gene cluster. Transcriptomic analysis revealed upregulation of hormone signaling and defense-related pathways, consistent with elevated levels of SA, JA, auxins, and cytokinins. The spl39 mutant exhibited enhanced resistance to bacterial blight with reduced lesion lengths and increased expression of defense-related genes. These findings highlight the role of large genomic deletions in reprogramming plant metabolism and immunity, providing new insights into the mechanisms underlying lesion mimic phenotypes and disease resistance in rice.